Imaging Atlas of the Pelvic Floor and Anorectal Diseases - Pescatori, Mario; Regadas, Francisco Sérgio Pinheiro; Murad Regadas, Sthela Maria; Zbar, Andrew P. (Springer Milan : Imprint: Springer, 2008)
Exciting technical advances in US, CT, and MRI over the past decade have greatly enhanced the challenging task of investigating intestinal, pelvic floor, and anorectal function and dysfunction. The goal of Imaging Atlas of the Pelvic Floor and Anorectal Diseases, edited and authored by internationally respected experts in the field, is to clearly and precisely present indications, techniques, limitations, sources of errors, and pitfalls of these imaging modalities. The concise text expertly describes the abundant, high-quality images that show the normal anorectal anatomy as well as the pathological appearance of the all-too-common large-bowel and pelvic floor functional diseases. The use of radiopaque markers in diagnosing colonic inertia; defecography, 3D US, and MRI in investigating obstructed defecation; 3D US and MRI in differentiating between benign and malignant anorectal neoplasms; CT and MRI in assessing pelviperineal anatomy and identifying pelvic tumors and inflammatory processes; and 2D and 3D US in determining appropriate treatment for fecal incontinence are discussed in depth. One of the atlas's strongest points is illustrating the use of 3D anorectal US with automatic scan in identifying complex anal fistula tracks, staging benign and malignant tumors, and postradiotherapy follow-up. Of particular importance is the description of novel dynamic techniques, such as dynamic transperineal US, in assessing pelvic floor functional diseases. Also importantly, this atlas demonstrates the value of a "team approach" between colorectal surgeons and radiologists for solving complex clinical disorders of the anorectum and pelvic floor.